Farmers’ Perceptions and Factors Influencing Combine Harvester Adoption in Langkap Village, Bangkalan Regency: Persepsi Petani dan Faktor-Faktor yang Mempengaruhi Adopsi Combine harvester di Desa Langkap Kabupaten Bangkalan - Durrotul Baidok; Nor Qomariyah; Teti Sugiarti (Jurnal Ilmiah Sosio Agribis, 2026)
This study was motivated by the importance of modern agricultural technology, particularly combine harvesters, to improve rice harvesting efficiency. However, adoption levels vary and are influenced by farmers' perceptions and socioeconomic characteristics. This study aimed to analyze farmers' perceptions and factors affecting combine harvester adoption in Langkap Village, Burneh District, Bangkalan Regency. A quantitative descriptive method was used, with data collected through questionnaires, interviews, and field observations involving 82 rice farmers who had used combine harvesters. Data were analyzed using descriptive analysis and ordinal logistic regression with SPSS. Results showed that farmers' perceptions were generally good regarding relative advantage, compatibility, and observability, but less favorable for complexity, and low for trialability. The overall adoption level was moderate to high, with trial and adoption indicators dominated by high categories, while awareness remained low. Ordinal logistic regression indicated that farmers' perception significantly affected adoption levels, whereas age, education, land size, and farming experience had no significant effect. These findings suggest that adoption decisions are driven more by perceived technology benefits than by socioeconomic characteristics. Therefore, efforts to increase adoption should focus on extension programs, field demonstrations, and opportunities for direct technology trials.